Developmwnt of mobile robot as base station for data collection in wireless sensor network - Mohd. Mazuan Harimon, 1988- author; Nurul Mu'azzah Abdul Latiff, supervisor; Fakulti Kejuruteraan Elektrik (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Telekomunikasi)) - Universiti Teknologi Malaysia, 2011